2023
DOI: 10.2217/fon-2022-0565
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of elderly patients with acute myeloid leukemia who receive no treatment in the Surveillance, Epidemiologyand End Results-Medicare database

Abstract: Background: Without treatment, acute myeloid leukemia (AML) is rapidly fatal. Nevertheless, a large proportion of elderly AML patients do not receive any treatment. Aim: To characterize the demographics, comorbidities, survival and prognostic factors of elderly AML patients who do not receive any AML treatment or supportive care (SC). Methods: A retrospective cohort analysis of the Surveillance, Epidemiology and End Results-Medicare database (2008–2015). Results: Of 7665 AML patients, 2373 (31%) did not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A nationwide population study in the Netherlands reported a similar survival rate of 14% between 2007–2012 [ 10 ]. According to more recent data from the SEER-Medicare database from 2008–2015, the treatment rate, encompassing both AML treatment and supportive care, rose to 69.04%, while the rate of AML treatment alone stood at 27.17% [ 11 ]. These results indicate an unmet need for AML treatment in older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide population study in the Netherlands reported a similar survival rate of 14% between 2007–2012 [ 10 ]. According to more recent data from the SEER-Medicare database from 2008–2015, the treatment rate, encompassing both AML treatment and supportive care, rose to 69.04%, while the rate of AML treatment alone stood at 27.17% [ 11 ]. These results indicate an unmet need for AML treatment in older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This includes a higher prevalence of aging-related vulnerabilities, such as physical and cognitive impairments that increase the risks of adverse events and mortality. 7 , 8 , 9 Therefore, older patients with AML and MDS often make treatment decisions with limited understanding of their diagnosis and lack of time for emotional coping.…”
Section: Introductionmentioning
confidence: 99%